Environmental Issues of Emerging Pangas (Pangasianodon hypophthalmus) Farming in Bangladesh - Anka, IZ; Faruk, MAR; Hasan, MM; Azad, MAK (Progressive Agriculture, 2014)
Pangas farming is one of the fastest growing types of aquaculture in Bangladesh. A study was conducted to understand environmental issues of emerging pangas farming in Bangladesh. Data were collected through questionnaire interview and focus group discussion (FGD) with pangas farmers. All together 40 farmers were interviewed and 6 FGD sessions were conducted in Muktagacha, Trishal and Valuka Upazila of Mymensingh district. Positive and negative aspects of environmental integrity were compared. Potential environmental impacts of pangas farming were assessed using certain parameters like land use pattern, water quality management and eutrophication, pond waste management, use of chemicals and antibiotics, and escape of fish. It was found that conversion of agricultural land and beels into pangas pond were remarkable which leads to the quick loss of agricultural land that reduces rice production. The unutilized feed portion accumulated in pangas ponds produced huge pond bottom waste and caused water quality deterioration. Eutrophication was found as a common problem along with discharge of highly nutrient rich water in the paddy field. Management of pond bottom waste was found quite poor though it has some good use in vegetable production in the pond dyke. Indiscriminate use of chemicals and antibiotics had an adverse impact on the environment and human health. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19118 Progress. Agric. 24(1&2): 159 - 170, 2013